Abscessed retroperitoneal hematoma as a late complication of adrenalectomy: a case report. - Carrillo - Barraza , S.; De la Cruz - Rivera, D.S (Revista de Ciencias Médicas Torreón, 2026)
Retroperitoneal hematoma is an uncommon complicationfollowing adrenalectomy; however, its progression to abscessrepresents a potentially life-threatening condition associatedwith high morbidity and mortality when diagnosis andtreatment are delayed. Clinical presentation is oftennonspecific, including fever without an identifiable source,abdominal or flank pain, and systemic inflammatoryresponse, which may delay early recognition. Predisposingfactors include recent surgical procedures, persistentundrained collections, and immunocompromised states,particularly in oncologic patients. Diagnosis relies on clinicalsuspicion supported by imaging studies, with computedtomography being the modality of choice to identifyretroperitoneal collections and signs of infection. Treatmentdepends on the patient’s clinical condition and characteristicsof the collection, requiring broad-spectrum antibiotic therapyand, in most cases, percutaneous or surgical drainage. Wepresent the case of a 76-year-old male with a history of rightnephrectomy for metastatic clear cell renal carcinoma andadrenalectomy,whodevelopedleftretroperitonealcollections suggestive of abscess, requiring specializedhospital management.